OPTIMIZACIJA STRUKTURE MORSKIH VEZOVA U NAUTICKOJ MARINI NA VIRU - Cerovic, Ljerka; Basic, Hrvoje (Poslovna izvrsnost, 2012)
Subject of research in this paper is to answer the questions, which sea berths and how many individual berths to plan in order to maximize the revenue from their renting, as the basic revenue of business activity of the nautical marina at Vir. The problem of research is to indicate on the incompleteness of existing project "Preliminary maritime solution of the construction of nautical marina on the island of Vir", brought as the part of Spatial Plan of regulation of the Municipality Vir. In this sense, the basic hypothesis of work is to prove that optimization of marine berths would change the structure of berths and increase the annual revenue of nautical marina at Vir. Predicting the number and structure of sea berths is based on the calculation of trend function for each group of berths, at first at level of needs of the Republic of Croatia, after which, based on the relative structure of berths in the Republic of Croatia, the Simplex method determines the optimal program of berths in the nautical marina at Vir. Finally, the obtained solution of objective function is checked and confirmed by Solver, Microsoft Office Excel tool for solving equations and for model optimization. [PUBLICATION ABSTRACT]